2020
DOI: 10.1515/remav-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Italian Auction Market: Features of Discounted Forced Sale Price

Abstract: The purpose of the paper is to investigate the main causes of discount between list price and forced sale value in the Italian real estate auction segment, in favor of more comprehensive determination of the value of mortgage underlying guarantees; this would allow for an improvement of further valorization processes of assets intended to obtain a higher selling price.Starting from the results of existing literature, an ordinary least squares regression analysis was conducted in order to point out the main det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Further studies focused on the nature of the asset (Donner et al, 2016;Donner, 2017). An interesting conceptual review was carried out (Renigied-Bilozor et al, 2018), while more recently the use of multiple regression models was proposed for the Italian reality (Amoruso et al, 2020;d'Amato and Kauko, 2009;d'Amato and Siniak, 2009;Di Liddo et al, 2022). The contribution is organized as follows: (i) description of some general aspects relating to the appraisal in real estate auctions; (ii) formal presentation of the model, based on additive form of the price function normally considered in the application of Market Comparison Approach (iii) an application of the model to a concrete case study; (iv) final remarks and future directions of research.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies focused on the nature of the asset (Donner et al, 2016;Donner, 2017). An interesting conceptual review was carried out (Renigied-Bilozor et al, 2018), while more recently the use of multiple regression models was proposed for the Italian reality (Amoruso et al, 2020;d'Amato and Kauko, 2009;d'Amato and Siniak, 2009;Di Liddo et al, 2022). The contribution is organized as follows: (i) description of some general aspects relating to the appraisal in real estate auctions; (ii) formal presentation of the model, based on additive form of the price function normally considered in the application of Market Comparison Approach (iii) an application of the model to a concrete case study; (iv) final remarks and future directions of research.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in order to analyze the correlation between the forced sale value and the urban and social context of the assets, factors considered as significantly intervening in the context of foreclosures included: socio-economic aspects regarding market trends, real estate and demographic factors (location, profitability in terms of employment, number of normalized transactions, population, real estate market intensity index); intrinsic factors (state of upkeep, technological characteristics, overall area); and aspects relating to the auction market (days spent at the auction, number of auctions, discount, premium and valuation date). In a recent study on judicial auctions in Southern Italy, Amoruso et al (2020) have shown that the timing of the procedures is the main cause of the discount on the hammer price compared to the estimated value. In its reports, the Bank of Italy presented a detailed examination of the long duration of the judicial credit recovery procedures in Italy, underlining the limited efficiency of these mechanisms, both in terms of time extension and in terms of recovered values (Giacomelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a study carried out on the segment of judicial auctions in Southern Italy, Amoruso et al (2020) have started from the analysis of a sample of proper-ties awarded at auction in the Apulia region to identify the excessive length of judicial procedures as the main cause of the erosion of value at auction. Del Giudice et al (2020) have implemented an analysis of the real estate auction sector in the Campania region, including variables that described the scenario generated following the Covid-19 pandemic -unemployment rate, family and per capita incomes, real estate dynamics -and evaluating their impact on medium and short-term trends in residential property prices, recording a reduction of 4.16% in the short term and 6.49% in the medium term (late 2020-early 2021).…”
Section: Introductionmentioning
confidence: 99%